2022
DOI: 10.1038/s41598-022-10591-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic chitosan stabilized Cu(II)-tetrazole complex: an effective nanocatalyst for the synthesis of 3-imino-2-phenylisoindolin-1-one derivatives under ultrasound irradiation

Abstract: In the present research, a recyclable catalyst has been prepared via a simple approach using chitosan as a linear polysaccharide. This paper reports the synthesis of novel copper(II) complex of 5-phenyl-1H-tetrazole immobilized on magnetic chitosan (MCS@PhTet@Cu(II)) as an effective catalyst. Transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), vibrating sample magnetometer (VSM), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), energy-dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although MOFs-based adsorbents provide some advantages, however, their tendency to aggregate and lose during the recovery process is considered a respective drawback for their applications 23 . Chitosan (Cs) is a natural, non-toxic, and inexpensive polysaccharide that with its unique physical and chemical properties including biocompatibility, biodegradability, flexibility, and various functional groups 24 , has been proposed as a substrate to prevent MOF agglomeration/aggregation in the present study. Furthermore, the presence of free hydroxyl and amino groups in chitosan structure and permission of their chemical modification can facilitate the adsorption of various types of pollutants in chitosan-derived nanocomposites 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Although MOFs-based adsorbents provide some advantages, however, their tendency to aggregate and lose during the recovery process is considered a respective drawback for their applications 23 . Chitosan (Cs) is a natural, non-toxic, and inexpensive polysaccharide that with its unique physical and chemical properties including biocompatibility, biodegradability, flexibility, and various functional groups 24 , has been proposed as a substrate to prevent MOF agglomeration/aggregation in the present study. Furthermore, the presence of free hydroxyl and amino groups in chitosan structure and permission of their chemical modification can facilitate the adsorption of various types of pollutants in chitosan-derived nanocomposites 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Nasrollahzadeh et al reported a synthetic procedure to access 3-imino-2-phenylisoindolin-1-one derivatives (58) using magnetic nanocatalysts, chitosan stabilised Cu(II)tetrazole complex (MCS@PhTet@Cu(II)) under ultrasoundirradiation from substituted phenylcyanamides (56) and benzoyl chloride (57) in ethanol at room temperature (Scheme 14). 68 The catalysts were obtained by coating Fe 3 O 4 NPs with chitosan followed by O-silylation using (3-chloropropyl)trimethoxysilane coupled with 5-phenyltetrazole and complexation using cupric chloride. The fully characterised catalysts were recycled in up to five catalytic runs with high efficacy, stability, and recyclability under external magnetism.…”
Section: Account Synlettmentioning
confidence: 99%